Pengembangan Aplikasi Sasaran Kinerja Pegawai (SKP) Guru berbasis Website di SMA Negeri 2 Sidrap Sulawesi Selatan - Muhammad Fachry Noorchoolish Arif; Denny Sagita Rusdianto; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
In Article 12 of the Republic of Indonesia Law Number 5 of 2014, it is explained that The Civil Servant is a profession that is responsible for planning, implementing, and supervising the implementation of government and national development tasks. In its implementation, it is required to apply professional policies and public services that are free from political interference and free from the practice of corruption, collusion, and nepotism. In monitoring the performance of Civil Servants, the Ministry of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia issued regulations written in Ministerial Regulation Number 8 of 2021 on the Civil Service Performance Management System. The Civil Service Performance Management System requires Civil Servants to prepare a document called the Employee Performance Target. At SMA Negeri 2 Sidrap South Sulawesi, the preparation of the documents is still done manually using Excel templates, which leads to problems such as frequent human error, difficulty in monitoring the progress, and because there is no time limit it allow data manipulation. From these problems, researcher were motivated to develop a website-based Teacher Employee Performance Target Application using the PHP programming language and the Laravel combined with TailwindCSS frameworks using the waterfall development method. This method begins with requrement analysis and engineering, designing system, implementation, and testing the system. Research resulted with the program successfully passed all established testing paths with valid results on 5 function samples. In addition, valid values were also generated from integration testing on 2 related components. The validation testing results on 31 functional requirements indicated that all valid test cases were successful and the compatibility testing showed that the system can be accessed through various web browsers without significant issues.